2020
DOI: 10.1159/000509878
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Internal Limiting Membrane Cleaning on Epiretinal Membrane Formation after Vitrectomy for Proliferative Diabetic Retinopathy

Abstract: Purpose: We hypothesised that cleaning the internal limiting membrane (ILM) with a flexible nitinol loop following diabetic vitrectomy without peeling may reduce the common occurrence of postoperative epiretinal membrane (ERM) formation. Methods: Consecutive patients undergoing vitrectomy for proliferative diabetic retinopathy by one surgeon from 2015 to 2019 were studied and divided into 2 cohorts: the control group underwent standard surgery, and the ILM clean group underwent additional cleaning of the macul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(43 reference statements)
0
1
0
2
Order By: Relevance
“…ILM peeling can significantly minimize this frequency. Recently, Mehta et al [12] reported that ILM cleaning without ILM peeling can reduce the incidence of ERM formation after vitrectomy for PDR compared with that after standard procedure (4% vs 20%; P=0.01). Lin et al [13] had reported that ILM peeling can treat diabetic macular edema, although this has been refuted by some studies [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…ILM peeling can significantly minimize this frequency. Recently, Mehta et al [12] reported that ILM cleaning without ILM peeling can reduce the incidence of ERM formation after vitrectomy for PDR compared with that after standard procedure (4% vs 20%; P=0.01). Lin et al [13] had reported that ILM peeling can treat diabetic macular edema, although this has been refuted by some studies [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…ВПМ, являясь одновременно базальной мембраной клеток Мюллера, зоной гиалоидо-ретинального контакта и непосредственно прилегая ко внутреннему гематоретинальному барьеру, интересна как в плане патогенеза витреоретинальных заболеваний, так и в качестве объекта хирургического воздействия. Изучение фрагментов ВПМ, полученных интраоперационно, проведено большинством из доступных методов оценки микроструктуры и гистологии: световой микроскопией с окрашиванием препаратов, различными формами электронной микроскопии, атомносиловой микроскопией и иными [11][12][13][14]. Авторами получены данные о структурных особенностях ВПМ, в частности о ее пористой неоднородной структуре, а также об особенностях витреальной и ретинальной поверхностей [13,14].…”
Section:  обсуждениеunclassified
“…Авторами получены данные о структурных особенностях ВПМ, в частности о ее пористой неоднородной структуре, а также об особенностях витреальной и ретинальной поверхностей [13,14]. Выявляемые на витреальной поверхности ВПМ остатки задней гиалоидной мембраны, как полагают, являются эпицентрами роста эпимакулярного фиброза [12,14]. Обнаруживаемые же на ретинальной поверхности фрагменты клеток Мюллера доказывают наличие микротравмирующего воздействия пилинга ВПМ на подлежащие слои и структурные элементы сетчатки [13,14].…”
Section:  обсуждениеunclassified